2013
DOI: 10.1158/1541-7786.mcr-12-0432
|View full text |Cite
|
Sign up to set email alerts
|

The Heterochronic microRNA let-7 Inhibits Cell Motility by Regulating the Genes in the Actin Cytoskeleton Pathway in Breast Cancer

Abstract: The heterochronic gene let-7 serves as a tumor suppressor microRNA by targeting various oncogenic pathways in cancer cells. Considerable evidence indicates that reduced expression of let-7 might be associated with poor clinical outcome in patients with cancer. Here, we report that the expression levels of three let-7 family members, let-7a, let-7b, and let-7g, were significantly decreased in the breast cancer patients with lymph node metastasis compared to those without lymph node metastasis. Enforced expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 49 publications
5
82
0
2
Order By: Relevance
“…Several studies have shown that the downregulation of let-7a is closely related to the abnormal potential in malignant tumors (13,25,26). However, the biological roles of let-7a in OS cells have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the downregulation of let-7a is closely related to the abnormal potential in malignant tumors (13,25,26). However, the biological roles of let-7a in OS cells have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ␣v␤8 integrin signals via the effector protein Band 4.1B during embryonic heart morphogenesis (66), likely in migratory cardiac neural crest cells. Primary tumors in the lung, mouth, skin, and other organs commonly upregulate ␤8 integrin gene expression during metastatic dispersal, and inhibition of integrin expression diminishes metastasis (67)(68)(69)(70). Hence, the ␣v␤8 integrin-PTP-PEST-RhoGDI1 signaling unit probably modulates leading edge dynamics and motility in divergent cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The let-7a-1/let-7d/let-7f-1 cluster (denoted as let-7adf cluster), with three members let-7a-1, let-7f-1, and let7d, is an important cluster of the let-7 family, accounting for about 25% of total let-7 precursors (Wang et al, 2011). Studies using various mouse models of cancer indicate that let-7 usually inhibits tumor growth in adult mice (Esquela-Kerscher et al, 2008;Hu et al, 2013;Wu et al, 2015). A handful of previous studies have also implicated let-7 in the regulation of glucose metabolism and amino acid sensing (Boyerinas et al, 2010;Dubinsky et al, 2014;Jiang and Baltimore, 2016;Nguyen and Zhu, 2015;Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%